Expectations of Undergraduate Students from Teachers in Learning Mathematics - Dhakal, Prem Kumari (Journal of Mathematics Education, 2023)
This paper aims to explore the expectations of the learners from teachers in learning mathematics in undergraduate level. This is a qualitative study and all the students of undergraduate mathematics programs of Mid-west University are the population of this study. The undergraduate program of Mid-West University is of four years with eight semesters, although the odd or even semesters run correspondingly in each six months due to the annual new admission system. Altogether twenty students (five students from each even semester) were selected purposively as the participants of this study. Open-end questions were the tool of gathering information. The questions were sent to each participant through messenger using a link of Google form. The data were analyzed thematically using six steps of thematic analysis. On the basis of the participants’ responses, it is concluded that the learners expect basic information, definitions, formula and relations before starting the new lesson in mathematics. Also, the learners expect motivation, support, basic concept as well as the opportunity to practice and discuss in the classroom to learn mathematics effectively. The findings of this study can be useful to the mathematics teachers of university level as well as the school level to teach mathematics on the basis of the learners’ expectations.